Skin wound bionic dressing and preparation method thereof
By designing a multi-layered biomimetic dressing, the problems of insufficient integration of structure and function and limited dynamic responsiveness of existing dressings have been solved, enabling rapid exudate management and intelligent drug release, thus promoting wound healing.
Patent Information
- Application Number
- CN202511479916.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2025-12-16
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing wound dressings lack biomimetic integration of structure and function, lack directional flow guidance structures, cannot efficiently manage excessive exudate, and have limited dynamic responsiveness and intelligence, making it difficult to achieve precise regulation of the wound healing process.
A biomimetic dressing for skin wounds was designed, comprising a sequentially cross-linked upper barrier layer, a middle functional layer, and a lower diversion layer. The functional layer is a drug-loaded nanofiber membrane, the diversion layer is a vertically oriented porous hydrogel layer, and the barrier layer is a photocrosslinked hydrogel layer. Intelligent drug release is achieved through pH-sensitive antibacterial agents and healing promoters linked by hydrazone bonds.
It achieves multi-level biomimicry in structure and function, rapidly adsorbs and drains wound exudate, provides biomimetic channels to promote wound healing, and has intelligent pH-responsive drug release and multiple antibacterial mechanisms to optimize the healing microenvironment.
Smart Images

Figure CN121130136A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of biomedical materials, and particularly relates to a skin wound bionic dressing and a preparation method thereof. BACKGROUND
[0002] Medical wound dressings are the core materials of wound care, and their main functions are to cover wounds, protect wounds, control exudates, prevent infection, and provide a suitable microenvironment for wound healing. Traditional dressings mainly play a simple covering and absorbing role, but are prone to adhesion with new granulation tissue, causing secondary damage when replaced, and are difficult to maintain a moist healing environment. With the progress of material science and medicine, dressings have evolved from passive covering to active participation, and various high-performance types have emerged: for example, hydrocolloid dressings can absorb a small amount of exudate and form a gel; alginate dressings form a gel when they come into contact with liquid, and have hemostatic effect; bioactive dressings integrate natural materials such as chitosan and collagen to promote cell migration and proliferation.
[0003] Although existing dressings have made great progress, there are still key problems that need to be improved. First, the bionic integration of structure and function is insufficient, and many dressings only focus on a single function, making it difficult to reproduce the gradient and integrated structure design of healthy skin in multiple layers; and there is a lack of bionic directional flow structure inside, which cannot efficiently manage excess exudate, leading to wound immersion. The invention patent with publication number CN118846188A uses a composite of a barrier layer, a hemostatic layer, and an antibacterial layer to prepare a dressing, but lacks a directional flow structure, which cannot ensure rapid absorption and storage of exudate; secondly, the dynamic responsiveness and intelligence are limited, wound healing is a complex dynamic process, and most existing dressings cannot sense and respond in real time to adjust the release rate of antibacterial factors or growth factors as needed, which easily leads to antibiotic abuse or mismatched release patterns with the healing stage. The invention patent with publication number CN118976135A uses bionic principles to prepare a dressing that can quickly drain wound exudate, but the drugs inside cannot respond intelligently, which easily leads to drug abuse or waste. Therefore, developing a high-efficiency wound repair material that combines bionic structure, intelligent response, and multi-functional synergy has become an important development direction in the field. SUMMARY
[0004] The purpose of the present application is to provide a skin wound bionic dressing and a preparation method thereof to solve the above technical problems.
[0005] To achieve the above technical purpose, the technical solution of the present application is: The skin wound biomimetic dressing is characterized by comprising an upper barrier layer, a middle functional layer and a lower flow guide layer which are cross-linked and stacked in sequence; the functional layer is a drug-loaded nanofiber membrane, which contains pH-sensitive antibacterial agents and healing promoters inside; the flow guide layer is a hydrogel layer with a vertically oriented porous structure; and the barrier layer is a photo-crosslinked hydrogel layer, which is dispersed with silver-loaded mesoporous silica nanoparticles.
[0006] As a further improvement, the pH-sensitive antibacterial agent is vanillin connected to polylactic acid-glycolic acid copolymer through a hydrazone bond; and the healing promoter is low molecular heparin or heparin sodium.
[0007] The application further provides a preparation method of the skin wound biomimetic dressing, comprising the following steps: S1, dissolving hyaluronic acid and healing promoters in deionized water to obtain an aqueous phase solution; dissolving polylactic acid-glycolic acid and poly-epsilon-caprolactone in dichloromethane to obtain an organic phase solution; adding vanillin hydrazone bond connected polymer into the organic phase solution and stirring to dissolve; slowly adding the aqueous phase solution into the organic phase solution, adding Span80, stirring to mix, performing emulsification at 0-4 DEG C to obtain an emulsion; using the emulsion to perform electrospinning to obtain a drug-loaded nanofiber membrane, i.e., the middle functional layer; S2, configuring 2% sodium alginate oxide solution and 2% modified gelatin solution, mixing, stirring for 1-2 h to obtain a mixed prepolymer solution; performing directional freezing on the mixed prepolymer solution to obtain a vertically porous prepolymer; immersing the vertically porous prepolymer in a CaCl2 solution, immediately spreading the vertically porous prepolymer on the drug-loaded nanofiber membrane, immersing in a 0.3% genipin aqueous solution, placing at 37 DEG C in the dark for 6-12 h, gently washing with deionized water, air-drying to obtain a double-layer structure dressing, i.e., the middle functional layer and the lower flow guide layer; S3, dissolving methacrylated gelatin in a sterile phosphate buffer solution to configure a 5% w / v solution; adding a photo initiator LAP, stirring to dissolve under light shielding conditions, adding silver-loaded mesoporous silica nanoparticles, performing ice bath ultrasonic to uniformly disperse the silver-loaded mesoporous silica nanoparticles to obtain a prepolymer solution; pouring the prepolymer solution on the surface of the double-layer structure dressing, the pouring position being the other side of the sodium alginate oxide and modified gelatin polymer film, spreading the prepolymer solution using a scraper, covering a layer of PET film, and performing ultraviolet crosslinking; removing the PET film after the crosslinking is completed to obtain a dressing sample, washing the dressing sample with a sterile phosphate buffer solution, sealing and packaging to obtain the skin wound biomimetic dressing.
[0008] As a further improvement, in step S1, the preparation method of the vanillin hydrazone-linked polymer is as follows: Polylactic acid-glycolic acid (PLGA) is dissolved in anhydrous DMSO to obtain a PLA solution; NHS and EDC·HCl are dissolved in anhydrous DMSO and added to the PLA solution. Under nitrogen protection, the reaction is carried out at room temperature for 6 hours to obtain a polymer activation solution; adipate dihydrazide is dissolved in anhydrous DMSO and added to the polymer activation solution, with a mass ratio of adipate dihydrazide to PLA of 5:1. The reaction is carried out at room temperature for 24 hours, precipitated with glacial ether, and dried to obtain a white powder; the white powder is dissolved in anhydrous DMSO, vanillin is added, and the pH is adjusted to 4-5 with glacial acetic acid. Under light protection and nitrogen protection, the reaction is carried out at 40°C with stirring for 36 hours to obtain a coupling solution; the coupling solution is dialyzed in the dark and then lyophilized to obtain the vanillin hydrazone-linked polymer; the specific reaction formula is as follows: ; ; As a further improvement, in step S1, the mass ratio of the added hyaluronic acid, healing agent, polylactic-co-glycolic acid, poly(ε-caprolactone), and vanillin hydrazone-linked polymerization is 1:0.5~1:30~40:3~5:10~15; the amount of Span80 added is 1% of the volume of dichloromethane; the electrospinning parameters are: ambient temperature of 25℃, humidity of 20~40%, voltage of 15~22kV, feed rate of 1.0~2.0mL / h, and receiving distance of 15~20cm.
[0009] As a further improvement, in step S2, the modified gelatin is prepared as follows: gelatin is dissolved in ultrapure water, heated and stirred in a 50°C water bath until dissolved, to prepare a 2% gelatin solution; fucoidan is dissolved in acetate-sodium acetate buffer solution to prepare a 2% fucoidan solution, NHS and EDC·HCl are added, and stirred at room temperature for 30 min to obtain a fucoidan activation solution; the fucoidan activation solution and gelatin solution are mixed in a volume ratio of 1:1, the pH is adjusted to 6.5~7.0 using NaOH, and the reaction is carried out at room temperature in the dark for 12~24 h under nitrogen protection, dialyzed in NaCl solution, then dialyzed in ultrapure water, and freeze-dried to obtain modified gelatin.
[0010] As a further improvement, in step S2, the volume ratio of the 2% sodium alginate oxidized solution to the 2% modified gelatin solution is 7:3; the directional freezing step is as follows: the mixed prepolymer liquid is poured into the mold, the mold is placed on the copper platform of the directional freezing device, and unidirectional freezing is performed from bottom to top. The cold source temperature is -78℃, the freezing time is 30~60min, and after the freezing is completed, it is quickly placed at -80℃ for 30min and then freeze-dried at -50℃ for 24~48h.
[0011] As a further improvement, in step S3, the preparation method of the silver-loaded mesoporous silica nanoparticles is as follows: Hexadecyltrimethylammonium bromide is dissolved in deionized water, ammonia is added, and the mixture is stirred at 80°C for 30 min. Tetraethyl orthosilicate is slowly added dropwise, with a molar ratio of tetraethyl orthosilicate to hexadecyltrimethylammonium bromide of 4-6:1. The reaction is continued at 80°C for 2 h. The white precipitate is collected by centrifugation, dispersed in a 0.1 mol / L hydrochloric acid solution, and extracted by reflux at 80°C for 24 h. After centrifugation, the precipitate is... Mesoporous silica nanoparticles were obtained by washing with anhydrous ethanol and deionized water and drying. The mesoporous silica nanoparticles were dispersed in deionized water, and 0.1 mol / L silver nitrate solution was added. The mixture was stirred at room temperature in the dark for 12 h. Then, 0.1 mol / L sodium borohydride solution was slowly added dropwise. The volume ratio of silver nitrate solution to sodium borohydride solution was 1:2~5. The reaction was continued in the dark for 2 h. The precipitate was collected by centrifugation, washed with deionized water, and dried under vacuum at 60 °C to obtain silver-loaded mesoporous silica nanoparticles.
[0012] As a further improvement, in step S3, the mass ratio of the photoinitiator LAP, silver-loaded mesoporous silica nanoparticles, and methacrylamide gelatin is 1:1:20; the specific parameters for the ultraviolet crosslinking are: wavelength of 365~410nm, and light intensity on the sample surface of 5~10mW / cm². 2 The irradiation time is 30~60s.
[0013] Due to the adoption of the above technical solution, the beneficial effects of the present invention are as follows: This invention provides a biomimetic dressing for skin wounds, achieving multi-layered biomimicry in both structure and function. The dressing mimics the three-layer structure of natural skin, consisting of a barrier layer, a functional layer, and a drainage layer stacked sequentially. The functional layer, acting as the core "soil," carries active ingredients, while the unique vertically oriented porous drainage layer, acting as the "roots," actively and rapidly absorbs and drains excess wound exudate upwards from the wound, preventing exudate buildup and maceration of surrounding tissues. Simultaneously, it provides biomimetic channels for cell migration and nutrient exchange, significantly optimizing the healing microenvironment. Through the synergy between the "roots" and the "soil," the skin wound is maintained in an optimal healing state, promoting wound healing.
[0014] This dressing possesses intelligent pH-responsive drug synergistic release capabilities. Through ingenious molecular design, using adipic acid dihydrazide as a "double connector," vanillin is linked to the PLGA polymer chain via pH-sensitive hydrazone bonds. These hydrazone bonds are stable in normal physiological environments but rapidly break in the weakly acidic environment of infected wounds, achieving targeted, on-demand release of vanillin. Healing promoters are mixed within the gaps in the fibrous membrane, enabling slow and continuous release to promote wound healing. The pH-sensitive vanillin synergistically works with heparin continuously released from the nanofibers to exert multiple effects, including immunomodulation, anti-inflammation, and healing promotion, achieving intelligent and precise treatment.
[0015] This dressing constructs a multi-layered antibacterial and biocompatibility-enhancing mechanism, integrating physical, chemical, and biological antibacterial strategies. The outermost barrier layer forms a dense network through photocrosslinking, physically blocking microorganisms. The silver-loaded mesoporous silica nanoparticles loaded within it continuously release silver ions, providing a potent and long-lasting chemical antibacterial effect. Meanwhile, the inner layer of fucoidan-modified gelatin significantly improves the material's cell compatibility and, through the immunomodulatory properties of fucoidan itself, potentially regulates the wound's inflammatory response, accelerating the healing process by both inhibiting infection and actively promoting regeneration. Attached Figure Description
[0016] Figure 1 This is an ATR-FTIR detection result diagram of the vanillin-hydrazone polymer prepared in Example 1; Figure 2 This is an ATR-FTIR detection result image of the modified gelatin prepared in Example 1; Figure 3 These are SEM scan results of each layer of the wound dressing prepared in Example 1. Figure a is the SEM scan image after the preparation of the middle functional layer is completed; Figure b is the cross-sectional SEM scan image of the lower drainage layer; Figure c is the longitudinal section SEM scan image of the lower drainage layer; and Figure d is the SEM scan image of the upper shielding layer. Figure 4 These are the results of the water absorption and swelling test of the wound dressings in Examples 1, 2, 1, 2, and 3. Figure 5 Figure 1 shows the release rate of vanillin in the wound dressings of Examples 3, 1, 2, and 4 under different pH conditions. Figure 2a shows the release rate at pH 5.0, and Figure 3b shows the release rate at pH 7.4. Figure 6 Figure 1 shows the cell compatibility test results of the wound dressings of Examples 1, 4 and Comparative Example 3. Figure 2a shows the OD value test results, and Figure 3b shows the cell viability test results. Figure 7This is a flow cytometry result of the immune modulation function detection of the wound dressings of Example 1 and Comparative Example 5. Figure 8 The figures show the experimental results of detecting the effect of wound dressings on cell scratch healing in Example 1 and Comparative Example 5. Figure 9 The figures show the experimental results of detecting the effect of the wound dressings of Example 1, Comparative Example 2, and Comparative Example 4 on wound healing in rats. Detailed Implementation
[0017] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0018] Example 1: A method for preparing a biomimetic dressing for skin wounds, comprising the following steps: 1. Dissolve 2g of polylactic-co-glycolic acid in 20mL of anhydrous dimethyl sulfoxide (DSMO) to obtain a polylactic-co-glycolic acid solution; add 0.1g of N-hydroxysuccinimide (NHS) and 0.15g of... 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl) was dissolved in 5 mL of anhydrous DMSO and added to a polylactic acid-glycolic acid solution. The mixture was reacted at room temperature for 6 h under nitrogen protection to obtain a polymer activation solution. 10 g of adipic acid dihydrazide was dissolved in 20 mL of anhydrous DMSO and added to the polymer activation solution. The mixture was reacted at room temperature for 24 h, and 40 mL of glacial ether was added. The mixture was stirred until a precipitate formed, collected by centrifugation, and dried to obtain a white powder. 0.5 g of the white powder was dissolved in 10 mL of anhydrous DMSO, and 0.1 g of vanillin was added. The pH was adjusted to 4 using glacial acetic acid. The mixture was reacted at 40 °C for 36 h under nitrogen protection, protected from light, to obtain a coupling solution. The coupling solution was dialyzed in the dark and then lyophilized to obtain a vanillin-hydrazone-linked polymer. The obtained product was analyzed by ATR-FTIR, and the results are shown in the figure. Figure 1 ; 2. Dissolve 20 mg of hyaluronic acid and 10 mg of low molecular weight heparin in 1 mL of deionized water, and vortex to dissolve, obtaining an aqueous solution. Dissolve 0.6 g of polylactic acid-glycolic acid and 0.06 g of poly(ε-caprolactone) in 10 mL of dichloromethane, and mix well to obtain an organic solution. Add 0.2 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix well, and emulsify using a high-speed homogenizer at 0°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 20%, voltage of 15 kV, feed rate of 1.0 mL / h, and receiving distance of 15 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 3. Dissolve 1.0g of gelatin in ultrapure water, heat in a 50℃ water bath with stirring until dissolved, and bring the volume to 50mL with ultrapure water to prepare a 2% gelatin solution; dissolve 1.0g of fucoidan in acetate-sodium acetate buffer solution (pH 5.0), bring the volume to 50mL with buffer solution to prepare a 2% fucoidan solution, and add 0.1g... NHS and 0.15 g EDC·HCl were stirred at room temperature for 30 min to obtain fucoidan activation solution. The fucoidan activation solution and gelatin solution were mixed at a volume ratio of 1:1, and the pH was adjusted to 6.5 with NaOH. The mixture was reacted at room temperature in the dark under nitrogen protection for 12 h. The resulting mixture was dialyzed in NaCl solution for 24 h, followed by dialyzed in ultrapure water for 24 h, with the solution changed every 8 h. The dialysis bag MWCO = 8000~14000 Da. After freeze-drying, modified gelatin was obtained. ATR-FTIR analysis was performed, and the results are shown below. Figure 2 ; 4. Prepare a 2% sodium alginate oxidized solution and a 2% modified gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of modified gelatin solution, heat to 50℃ and mix evenly, stir for 1 h to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold, place the mold on the copper platform of the directional freezing device, and perform unidirectional freezing from bottom to top. The cold source temperature is -78℃ and the freezing time is 30 min. After the freezing is completed, quickly place the sample at -80℃ for 30 min and freeze-dry at -50℃ for 24 h until the ice crystals are completely removed to obtain a vertical porous prepolymer. Immerse the vertical porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and let it stand at 37℃ in the dark for 6 h. Rinse gently with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 5. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.14 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 6. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate oxidized and modified gelatin polymer film, spread the prepolymer solution with a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 365nm, sample surface light intensity 10mW / cm². 2 The irradiation time was 30 seconds. After the irradiation, the PET film was removed, the dressing was rinsed with sterile phosphate buffer, and then sealed and packaged to obtain a biomimetic dressing for skin wounds.
[0019] Example 2: A method for preparing a biomimetic dressing for skin wounds, the specific steps of which are as follows: 1. Dissolve 3g of polylactic acid-glycolic acid in 30mL of anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; dissolve 0.15g of NHS and 0.23g of EDC·HCl in 5mL of anhydrous DMSO, add them to the polylactic acid-glycolic acid solution, and react at room temperature for 6h under nitrogen protection to obtain a polymer activation solution; dissolve 15g of adipic acid dihydrazide in 20mL of anhydrous DMSO, add it to the polymer activation solution, and react at room temperature for 24h; add 40mL of glacial ether, stir until a precipitate appears, collect the precipitate, and dry it to obtain a white powder; dissolve 0.5g of the white powder in 10mL of anhydrous DMSO, add 0.1g of vanillin, adjust the pH to 5 with glacial acetic acid, and react at 40℃ for 36h under nitrogen protection in the dark to obtain a coupling solution; dialyze the coupling solution in the dark, freeze-dry it, and obtain a vanillin hydrazone-linked polymer; 2. Dissolve 20 mg of hyaluronic acid and 20 mg of low molecular weight heparin in 1.5 mL of deionized water and vortex to obtain an aqueous solution. Dissolve 0.8 g of polylactic acid-glycolic acid and 0.1 g of poly(ε-caprolactone) in 10 mL of dichloromethane and mix to obtain an organic solution. Add 0.3 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix, and emulsify using a high-speed homogenizer at 4°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 40%, voltage of 22 kV, feed rate of 2.0 mL / h, and receiving distance of 20 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 3. Dissolve 1.0 g of gelatin in ultrapure water, heat and stir in a 50°C water bath until dissolved, and dilute to 50 mL with ultrapure water to prepare a 2% gelatin solution. Dissolve 1.0 g of fucoidan in an acetate-sodium acetate buffer solution with a pH of 5.0, and dilute to 50 mL with the buffer solution to prepare a 2% fucoidan solution. Add 0.1 g of NHS and 0.15 g of EDC·HCl, stir at room temperature for 30 min to obtain an activated fucoidan solution. Mix the activated fucoidan solution and gelatin solution at a volume ratio of 1:1, adjust the pH to 7.0 with NaOH, and react at room temperature in the dark for 24 h under nitrogen protection. Dialyze the mixture after reaction in NaCl solution for 24 h, and then dialyze in ultrapure water for 24 h, changing the solution every 8 h. The dialysis bag MWCO = 8000~14000 Da. After freeze-drying, obtain modified gelatin. 4. Prepare a 2% sodium alginate oxidized solution and a 2% modified gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of modified gelatin solution, heat to 50℃ and mix evenly, stir for 2 hours to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold, place the mold on the copper platform of a directional freezing device, and perform unidirectional freezing from bottom to top. The cold source temperature is -78℃ and the freezing time is 60 min. After the freezing is completed, quickly place the sample at -80℃ for 30 min and freeze-dry at -50℃ for 48 h until the ice crystals are completely removed to obtain a vertical porous prepolymer. Immerse the vertical porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and stand at 37℃ in the dark for 12 h. Rinse gently with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 5. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.72 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 6. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate and modified gelatin polymer film, spread the prepolymer solution with a spatula, cover with a PET film, and then perform ultraviolet crosslinking with the following parameters: wavelength 410nm, sample surface light intensity 5mW / cm². 2 The irradiation time was 60 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed, and packaged to obtain a biomimetic dressing for skin wounds.
[0020] Example 3: A method for preparing a biomimetic dressing for skin wounds, the specific steps of which are as follows: 1. Dissolve 2g of polylactic acid-glycolic acid in 20mL of anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; dissolve 0.1g of NHS and 0.15g of EDC·HCl in 5mL of anhydrous DMSO, add them to the polylactic acid-glycolic acid solution, and react at room temperature for 6h under nitrogen protection to obtain a polymer activation solution; dissolve 10g of adipic acid dihydrazide in 20mL of anhydrous DMSO, add it to the polymer activation solution, react at room temperature for 24h, add 40mL of icy diethyl ether, a precipitate appears, and after drying, a white powder is obtained; dissolve 0.5g of the white powder in 10mL of anhydrous DMSO, add 0.1g of vanillin, adjust the pH to 4.5 with icy acetic acid, and react at 40℃ for 36h under nitrogen protection in the dark to obtain a coupling solution; dialyze the coupling solution in the dark, and freeze-dry it to obtain a vanillin hydrazone-linked polymer; 2. Dissolve 20 mg of hyaluronic acid and 14 mg of sodium heparin in 1 mL of deionized water, vortex to dissolve, and obtain an aqueous solution; dissolve 0.7 g of polylactic-co-glycolic acid and 0.08 g of poly(ε-caprolactone) in 10 mL of dichloromethane, mix well, and obtain an organic solution; add 0.34 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve; slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix, and emulsify using a high-speed homogenizer at 2°C, 12000 rpm for 2 min to obtain an emulsion; use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 30%, voltage of 18 kV, feed rate of 1.5 mL / h, and receiving distance of 18 cm; after spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane; 3. Dissolve 1.0 g of gelatin in ultrapure water, heat and stir in a 50°C water bath until dissolved, and dilute to 50 mL with ultrapure water to prepare a 2% gelatin solution. Dissolve 1.0 g of fucoidan in an acetate-sodium acetate buffer solution with a pH of 5.0, and dilute to 50 mL with the buffer solution to prepare a 2% fucoidan solution. Add 0.1 g of NHS and 0.15 g of EDC·HCl, stir at room temperature for 30 min to obtain an activated fucoidan solution. Mix the activated fucoidan solution and gelatin solution at a volume ratio of 1:1, adjust the pH to 6.8 with NaOH, and react at room temperature in the dark for 20 h under nitrogen protection. Dialyze the mixture after reaction in NaCl solution for 24 h, and then dialyze in ultrapure water for 24 h, changing the solution every 8 h. The dialysis bag MWCO = 8000~14000 Da. After freeze-drying, obtain modified gelatin. 4. Prepare a 2% sodium alginate oxidized solution and a 2% modified gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of modified gelatin solution, heat to 50℃ and mix evenly, stir for 1.5 h to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold, place the mold on the copper platform of the directional freezing device, and perform unidirectional freezing from bottom to top. The cold source temperature is -78℃ and the freezing time is 45 min. After the freezing is completed, quickly place the sample at -80℃ for 30 min and freeze-dry at -50℃ for 36 h until the ice crystals are completely removed to obtain a vertical porous prepolymer. Immerse the vertical porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and let it stand at 37℃ in the dark for 8 h. Rinse gently with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 5. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.20 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 5.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 6. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate and modified gelatin polymer film, spread the prepolymer solution using a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 385nm, sample surface light intensity 8mW / cm². 2 The irradiation time was 45 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed, and packaged to obtain a biomimetic dressing for skin wounds.
[0021] Comparative Example 1: A method for preparing a biomimetic dressing for skin wounds, differing from Example 1 in that it lacks a lower guiding layer, i.e., it lacks oxidized sodium alginate and modified gelatin layers. The specific steps are as follows: 1. Dissolve 2g of polylactic acid-glycolic acid in 20mL of anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; dissolve 0.1g of NHS and 0.15g of EDC·HCl in 5mL of anhydrous DMSO, add them to the polylactic acid-glycolic acid solution, and react at room temperature for 6h under nitrogen protection to obtain a polymer activation solution; dissolve 10g of adipic acid dihydrazide in 20mL of anhydrous DMSO, add it to the polymer activation solution, react at room temperature for 24h, add 40mL of icy diethyl ether, a precipitate appears, and after drying, a white powder is obtained; dissolve 0.5g of the white powder in 10mL of anhydrous DMSO, add 0.1g of vanillin, adjust the pH to 4 with icy acetic acid, and react at 40℃ for 36h under nitrogen protection in the dark to obtain a coupling solution; dialyze the coupling solution in the dark, and freeze-dry it to obtain a vanillin hydrazone-linked polymer; 2. Dissolve 20 mg of hyaluronic acid and 10 mg of low molecular weight heparin in 1 mL of deionized water, and vortex to dissolve, obtaining an aqueous solution. Dissolve 0.6 g of polylactic acid-glycolic acid and 0.06 g of poly(ε-caprolactone) in 10 mL of dichloromethane, and mix well to obtain an organic solution. Add 0.2 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix well, and emulsify using a high-speed homogenizer at 0°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 20%, voltage of 15 kV, feed rate of 1.0 mL / h, and receiving distance of 15 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 3. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.14 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 4. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ultrasonication in an ice bath to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer structure dressing, spread the prepolymer solution using a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 365nm, sample surface light intensity 10mW / cm². 2 The irradiation time was 30 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed and packaged to obtain a biomimetic dressing for skin wounds.
[0022] Comparative Example 2: A method for preparing a biomimetic dressing for skin wounds, differing from Example 1 in that the lower guiding layer was not subjected to directional freezing, i.e., the oxidized sodium alginate and modified gelatin layers were not subjected to directional freezing. The specific steps are as follows: 1. Dissolve 2g of polylactic acid-glycolic acid in 20mL of anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; dissolve 0.1g of NHS and 0.15g of EDC·HCl in 5mL of anhydrous DMSO, add them to the polylactic acid-glycolic acid solution, and react at room temperature for 6h under nitrogen protection to obtain a polymer activation solution; dissolve 10g of adipic acid dihydrazide in 20mL of anhydrous DMSO, add it to the polymer activation solution, react at room temperature for 24h, add 40mL of icy diethyl ether, a precipitate appears, and after drying, a white powder is obtained; dissolve 0.5g of the white powder in 10mL of anhydrous DMSO, add 0.1g of vanillin, adjust the pH to 4 with icy acetic acid, and react at 40℃ for 36h under nitrogen protection in the dark to obtain a coupling solution; dialyze the coupling solution in the dark, and freeze-dry it to obtain a vanillin hydrazone-linked polymer; 2. Dissolve 20 mg of hyaluronic acid and 10 mg of low molecular weight heparin in 1 mL of deionized water, and vortex to dissolve, obtaining an aqueous solution. Dissolve 0.6 g of polylactic acid-glycolic acid and 0.06 g of poly(ε-caprolactone) in 10 mL of dichloromethane, and mix well to obtain an organic solution. Add 0.2 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix well, and emulsify using a high-speed homogenizer at 0°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 20%, voltage of 15 kV, feed rate of 1.0 mL / h, and receiving distance of 15 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 3. Dissolve 1.0 g of gelatin in ultrapure water, heat and stir in a 50°C water bath until dissolved, and dilute to 50 mL with ultrapure water to prepare a 2% gelatin solution. Dissolve 1.0 g of fucoidan in an acetate-sodium acetate buffer solution with a pH of 5.0, and dilute to 50 mL with the buffer solution to prepare a 2% fucoidan solution. Add 0.1 g of NHS and 0.15 g of EDC·HCl, stir at room temperature for 30 min to obtain an activated fucoidan solution. Mix the activated fucoidan solution and gelatin solution at a volume ratio of 1:1, adjust the pH to 6.5 with NaOH, and react at room temperature in the dark for 12 h under nitrogen protection. Dialyze the mixture after reaction in NaCl solution for 24 h, and then dialyze in ultrapure water for 24 h, changing the solution every 8 h. The dialysis bag MWCO = 8000~14000 Da. After freeze-drying, obtain modified gelatin. 4. Prepare a 2% sodium alginate oxidized solution and a 2% modified gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of modified gelatin solution, heat to 50℃ and mix evenly, stir for 1 h to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold and place it directly at -80℃ for 30 min, then freeze-dry at -50℃ for 24 h until all ice crystals are completely removed to obtain a porous prepolymer. Immerse the porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and let it stand at 37℃ in the dark for 6 h. Gently rinse with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 5. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.14 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 6. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate and modified gelatin polymer film, spread the prepolymer solution using a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 365nm, sample surface light intensity 10mW / cm². 2 The irradiation time was 30 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed and packaged to obtain a biomimetic dressing for skin wounds.
[0023] Comparative Example 3: A method for preparing a biomimetic dressing for skin wounds, differing from Example 1 in that the gelatin in the lower guiding layer was not modified. The specific steps are as follows: 1. Dissolve 2g of polylactic acid-glycolic acid in 20mL of anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; dissolve 0.1g of NHS and 0.15g of EDC·HCl in 5mL of anhydrous DMSO, add them to the polylactic acid-glycolic acid solution, and react at room temperature for 6h under nitrogen protection to obtain a polymer activation solution; dissolve 10g of adipic acid dihydrazide in 20mL of anhydrous DMSO, add it to the polymer activation solution, react at room temperature for 24h, add 40mL of icy diethyl ether, a precipitate appears, and after drying, a white powder is obtained; dissolve 0.5g of the white powder in 10mL of anhydrous DMSO, add 0.1g of vanillin, adjust the pH to 4 with icy acetic acid, and react at 40℃ for 36h under nitrogen protection in the dark to obtain a coupling solution; dialyze the coupling solution in the dark, and freeze-dry it to obtain a vanillin hydrazone-linked polymer; 2. Dissolve 20 mg of hyaluronic acid and 10 mg of low molecular weight heparin in 1 mL of deionized water, and vortex to dissolve, obtaining an aqueous solution. Dissolve 0.6 g of polylactic acid-glycolic acid and 0.06 g of poly(ε-caprolactone) in 10 mL of dichloromethane, and mix well to obtain an organic solution. Add 0.2 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix well, and emulsify using a high-speed homogenizer at 0°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 20%, voltage of 15 kV, feed rate of 1.0 mL / h, and receiving distance of 15 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 3. Prepare a 2% sodium alginate oxidized solution and a 2% gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of gelatin solution, heat to 50℃ and mix evenly, stir for 1 h to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold, place the mold on the copper platform of the directional freezing device, and perform unidirectional freezing from bottom to top. The cold source temperature is -78℃ and the freezing time is 30 min. After the freezing is completed, quickly place the sample at -80℃ for 30 min and freeze-dry for 24 h until the ice crystals are completely removed to obtain a vertical porous prepolymer. Immerse the vertical porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and let it stand at 37℃ in the dark for 6 h. Rinse gently with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 4. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.14 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 5. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate and modified gelatin polymer film, spread the prepolymer solution using a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 365nm, sample surface light intensity 10mW / cm². 2 The irradiation time was 30 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed and packaged to obtain a biomimetic dressing for skin wounds.
[0024] Comparative Example 4: A method for preparing a biomimetic dressing for skin wounds, differing from Example 1 in that vanillin was not subjected to pH-sensitive modification. The specific steps are as follows: 1. Dissolve 20 mg hyaluronic acid, 10 mg low molecular weight heparin, and 0.2 g vanillin in 5 mL of deionized water and vortex to dissolve, obtaining an aqueous solution. Dissolve 0.6 g polylactic acid-glycolic acid and 0.06 g poly-ε-caprolactone in 10 mL of dichloromethane and mix well to obtain an organic solution. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix, and emulsify using a high-speed homogenizer at 0°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 20%, voltage of 15 kV, feed rate of 1.0 mL / h, and receiving distance of 15 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 2. Dissolve 1.0 g of gelatin in ultrapure water, heat and stir in a 50°C water bath until dissolved, and dilute to 50 mL with ultrapure water to prepare a 2% gelatin solution. Dissolve 1.0 g of fucoidan in an acetate-sodium acetate buffer solution with a pH of 5.0, and dilute to 50 mL with the buffer solution to prepare a 2% fucoidan solution. Add 0.1 g of NHS and 0.15 g of EDC·HCl, stir at room temperature for 30 min to obtain an activated fucoidan solution. Mix the activated fucoidan solution and gelatin solution at a volume ratio of 1:1, adjust the pH to 6.5 with NaOH, and react at room temperature in the dark for 12 h under nitrogen protection. Dialyze the mixture after reaction in NaCl solution for 24 h, and then dialyze in ultrapure water for 24 h, changing the solution every 8 h. The dialysis bag MWCO = 8000~14000 Da. After freeze-drying, obtain modified gelatin. 3. Prepare a 2% sodium alginate oxidized solution and a 2% modified gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of modified gelatin solution, heat to 50℃ and mix evenly, stir for 1 h to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold, place the mold on the copper platform of a directional freezing device, and perform unidirectional freezing from bottom to top. The cold source temperature is -78℃ and the freezing time is 30 min. After the freezing is completed, quickly place the sample at -80℃ for 30 min and freeze-dry at -50℃ for 24 h until the ice crystals are completely removed to obtain a vertical porous prepolymer. Immerse the vertical porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and let it stand at 37℃ in the dark for 6 h. Rinse gently with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 4. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.14 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 5. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate and modified gelatin polymer film, spread the prepolymer solution using a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 365nm, sample surface light intensity 10mW / cm². 2 The irradiation time was 30 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed and packaged to obtain a biomimetic dressing for skin wounds.
[0025] Comparative Example 5: A method for preparing a biomimetic dressing for skin wounds, differing from Example 1 in that low molecular weight heparin was not added. The specific steps are as follows: 1. Dissolve 2g of polylactic acid-glycolic acid in 20mL of anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; dissolve 0.1g of NHS and 0.15g of EDC·HCl in 5mL of anhydrous DMSO, add them to the polylactic acid-glycolic acid solution, and react at room temperature for 6h under nitrogen protection to obtain a polymer activation solution; dissolve 10g of adipic acid dihydrazide in 20mL of anhydrous DMSO, add it to the polymer activation solution, react at room temperature for 24h, add 40mL of icy diethyl ether, a precipitate appears, and after drying, a white powder is obtained; dissolve 0.5g of the white powder in 10mL of anhydrous DMSO, add 0.1g of vanillin, adjust the pH to 4 with icy acetic acid, and react at 40℃ for 36h under nitrogen protection in the dark to obtain a coupling solution; dialyze the coupling solution in the dark, and freeze-dry it to obtain a vanillin hydrazone-linked polymer; 2. Dissolve 20 mg of hyaluronic acid in 1 mL of deionized water and vortex to obtain an aqueous solution. Dissolve 0.6 g of polylactic acid-glycolic acid and 0.06 g of poly(ε-caprolactone) in 10 mL of dichloromethane and mix well to obtain an organic solution. Add 0.2 g of vanillin hydrazone-linked polymer to the organic solution and stir to dissolve. Slowly add the aqueous solution to the organic solution, add 0.1 mL of Span 80, stir to mix well, and emulsify using a high-speed homogenizer at 0°C, 10000 rpm for 3 min to obtain an emulsion. Use the emulsion for electrospinning at an ambient temperature of 25°C, humidity of 20%, voltage of 15 kV, feed rate of 1.0 mL / h, and receiving distance of 15 cm. After spinning, allow the fiber membrane to stand and dry to obtain a drug-loaded nanofiber membrane. 3. Dissolve 1.0 g of gelatin in ultrapure water, heat and stir in a 50°C water bath until dissolved, and dilute to 50 mL with ultrapure water to prepare a 2% gelatin solution. Dissolve 1.0 g of fucoidan in an acetate-sodium acetate buffer solution with a pH of 5.0, and dilute to 50 mL with the buffer solution to prepare a 2% fucoidan solution. Add 0.1 g of NHS and 0.15 g of EDC·HCl, stir at room temperature for 30 min to obtain an activated fucoidan solution. Mix the activated fucoidan solution and gelatin solution at a volume ratio of 1:1, adjust the pH to 6.5 with NaOH, and react at room temperature in the dark for 12 h under nitrogen protection. Dialyze the mixture after reaction in NaCl solution for 24 h, and then dialyze in ultrapure water for 24 h, changing the solution every 8 h. The dialysis bag MWCO = 8000~14000 Da. After freeze-drying, obtain modified gelatin. 4. Prepare a 2% sodium alginate oxidized solution and a 2% modified gelatin solution using deionized water. Take 70 mL of sodium alginate oxidized solution and 30 mL of modified gelatin solution, heat to 50℃ and mix evenly, stir for 1 h to obtain a mixed prepolymer solution. Pour the mixed prepolymer solution into a mold, place the mold on the copper platform of the directional freezing device, and perform unidirectional freezing from bottom to top. The cold source temperature is -78℃ and the freezing time is 30 min. After the freezing is completed, quickly place the sample at -80℃ for 30 min and freeze-dry at -50℃ for 24 h until the ice crystals are completely removed to obtain a vertical porous prepolymer. Immerse the vertical porous prepolymer in a 5% w / v CaCl2 solution, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, immerse the whole in a 0.3% genipin aqueous solution, and let it stand at 37℃ in the dark for 6 h. Rinse gently with deionized water and air dry in a fume hood to obtain a double-layer structure dressing. 5. Dissolve 0.5 g of hexadecyltrimethylammonium bromide in deionized water, add ammonia, stir at 80℃ for 30 min, slowly add 1.14 g of tetraethyl orthosilicate, continue the reaction at 80℃ for 2 h, collect the white precipitate by centrifugation, disperse the white precipitate in 0.1 mol / L hydrochloric acid solution, reflux extract at 80℃ for 24 h, centrifuge, wash the precipitate with anhydrous ethanol and deionized water, and dry to obtain mesoporous silica nanoparticles; disperse 100 mg of the particle product in 50 mL of deionized water, sonicate to mix, add 1.5 mL of 0.1 mol / L silver nitrate solution, stir at room temperature in the dark for 12 h, slowly add 3.0 mL of 0.1 mol / L sodium borohydride solution, continue the reaction in the dark for 2 h, collect the precipitate by centrifugation, wash with deionized water, and vacuum dry at 60℃ to obtain silver-loaded mesoporous silica nanoparticles; 6. Dissolve 0.5g of methacrylamide gelatin in 10mL of sterile phosphate buffer; add 25mg of photoinitiator LAP, stir until dissolved under light-protected conditions, add 25mg of silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the nanoparticles, obtaining a prepolymer solution; pour the prepolymer solution onto the surface of the bilayer dressing, on the other side of the sodium alginate and modified gelatin polymer film, spread the prepolymer solution using a spatula, cover with a PET film, and then perform ultraviolet light crosslinking. The specific parameters are: wavelength 365nm, sample surface light intensity 10mW / cm². 2 The irradiation time was 30 seconds. After the irradiation, the sample was rinsed with sterile phosphate buffer, sealed and packaged to obtain a biomimetic dressing for skin wounds.
[0026] The prepared dressing was subjected to various performance tests, the specific process of which is as follows: (1) SEM observation of dressings The morphology of each thin film layer during the preparation process in Example 1 was observed using scanning electron microscopy. The SEM results are as follows: Figure 3 As shown in the figure; Figure a is the SEM scan image after the middle functional layer is fabricated; Figure b is the cross-sectional SEM scan image of the lower guide layer; Figure c is the longitudinal section SEM scan image of the lower guide layer; Figure d is the SEM scan image of the upper shielding layer.
[0027] from Figure 3 As can be seen, the middle functional layer has a uniform and irregular mesh structure, indicating that the middle functional layer is a membrane structure made of interwoven fibers; the lower layer has a pore structure of varying sizes in cross-section and a tubular structure in longitudinal section, indicating that the lower layer has a pore structure with obvious directionality; the upper shielding layer is relatively dense and flat, with a large number of nanoparticles visible on the surface and inside; the three-layer biomimetic wound dressing prepared by this invention, through the cooperation of a dense antibacterial barrier layer, a drug-loaded fiber functional layer, and a vertical drainage layer for rapid drainage, simulates some functions of healthy skin, thereby achieving efficient biomimetic repair of wounds.
[0028] (2) Water absorption and swelling The prepared wound dressing sample was cut into equal sizes and weighed to obtain W0. The wound dressing was then immersed in PBS buffer at 37°C for static immersion. At a preset time point, the wound dressing was removed from the PBS buffer, excess liquid was wiped off with filter paper, and the sample was immediately weighed to obtain Wt. The swelling rate was calculated using the formula: Swelling rate (%) = (Wt - W0) / W0 × 100%, where Wt and W0 are the masses of the sample after immersion time t and before PBS immersion, respectively. The experimental results are as follows: Figure 4 As shown.
[0029] from Figure 4As can be seen, the wound dressings of Examples 1 and 2 rapidly absorbed water and swelled within 1 hour, with a swelling rate exceeding 100%. In contrast, the water absorption capacity of Comparative Examples 1 to 3 was significantly poor. Comparative Example 1, lacking a lower guiding layer, could not rapidly absorb water through it, and its maximum water absorption and swelling capacity was also low, less than 200%, also due to the absence of a lower guiding layer. Comparative Example 2, lacking vertical orientation of the lower guiding layer, had insufficient rapid water absorption capacity. Comparative Example 3, without modification of the gelatin, lacked the cross-linking network of gelatin and fucoidan, resulting in lower swelling performance compared to the wound dressings prepared in the examples.
[0030] During the healing process, wounds produce exudate. Excessive exudate can damage the skin, accelerate bacterial infection, and increase patient pain. Therefore, wound dressings must have the ability to quickly absorb water and lock in large amounts of exudate. The wound dressing prepared by this patented method can quickly absorb wound exudate through capillary action in vertical channels, and has a strong swelling capacity to lock in the liquid, prevent exudate leakage, and promote rapid wound healing.
[0031] (3) Drug release under different pH conditions Cut wound dressings of the same size and soak them in physiological saline at pH 7.4 (simulating normal tissue) and pH 5.0 (simulating infected / inflammatory wounds), respectively. They were then left to stand at 37°C and samples were taken at predetermined time points. After centrifugation, the absorbance of the supernatant was measured to calculate the release rate of vanillin. The experimental results are shown in Figure 5.
[0032] from Figure 5 As can be seen, wound dressings soaked in physiological saline at pH 5.0 achieved a release rate of over 90% within 12 hours and a release rate of 50% within 2 hours. However, wound dressings soaked in physiological saline at pH 7.4, using pH-sensitive hydrazone linkages in Examples 3, 1, and 2, showed very low release rates, remaining below 8% at 168 hours and below 5% at 48 hours, indicating that vanillin release is very slow at pH 7.4. In contrast, Comparative Example 4 did not use hydrazone linkages for vanillin, and therefore its wound dressing achieved a drug release rate of approximately 80% within 24 hours, indicating that the vanillin molecule release in Comparative Example 4 did not exhibit pH-responsive characteristics.
[0033] (4) Cell compatibility Cell compatibility experiments were conducted using mouse fibroblast L929 cells for different wound dressings. Cells were cultured normally to the logarithmic growth phase and seeded into 48-well plates, 10 cells per well. 4Cells were cultured until they adhered to the culture dish. The wound dressing was sterilized by UV irradiation for 15 minutes and then gently placed into the culture dish for direct contact with the cells. The cells were then cultured normally. On days 1, 4, and 7 of cell culture, the wound dressing was removed from the wells for CCK8 assay and viability testing. The experimental results are as follows: Figure 6 As shown.
[0034] from Figure 6 As can be seen, Examples 1 and 4 basically did not affect the normal proliferation of L929 cells, and the cell viability decreased slightly, but the decrease was very small, indicating that the cytotoxicity of the wound dressings of Examples 1 and 4 was within an acceptable range; however, the wound dressing of Comparative Example 3 showed a significant inhibition of cell proliferation on the 4th day, with a proliferation rate significantly lower than that of the control group, and the cell viability also decreased to about 70%, indicating that the wound dressing of Comparative Example 3 inhibited fibroblast proliferation and had a certain degree of cytotoxicity.
[0035] Wound dressings, needing to adhere closely to broken skin, must possess good biocompatibility. Otherwise, they will not only fail to promote wound healing but may also hinder the normal proliferation of wound cells, thus impairing healing. During our research, we discovered that gelatin has poor biocompatibility, affecting normal cell proliferation. However, by modifying gelatin with fucoidan, we introduced abundant active groups such as hydroxyl, carboxyl, and sulfate esters, altering the chemical properties of gelatin, enhancing its hydrophilicity, and improving the charge distribution on its surface, thereby improving the biocompatibility of the wound dressing.
[0036] (5) Detection of immune cell regulation An in vitro inflammation model was established by stimulating macrophages with LPS (lipopolysaccharide) to polarize them to the M1 phenotype. Wound dressings of the same size were cut and soaked in 1 mL of pH 5.0 PBS buffer for 4 hours. The pH was then adjusted to 7.4, and the soaking solution was added to the cell culture medium for the corresponding groups. The control group and the LPS polarization group used the same volume of PBS buffer. Flow cytometry was used for analysis, and the results are shown below. Figure 7 .
[0037] from Figure 7 As can be seen, the wound dressing soaking solution of Example 1 can transform immune cells into M2 cells, while the proportion of M2 cells in Comparative Example 5 is lower than that in Example 1. This indicates that the wound dressing of Example 1 can regulate the polarity of macrophages, causing them to transform into anti-inflammatory functions, which is beneficial for treating wound inflammation and promoting wound healing.
[0038] (6) Healing promotion ability test: cell scratch test L929 fibroblasts were cultured until they adhered to the culture dish and covered the bottom. The cells were then scratched, and photographs were taken to record the results. Wound dressings of the same size were cut, sterilized with UV light, and gently placed on the scratched areas at the bottom of the culture dish. Culture continued, and the wound healing process was observed by taking photographs at specified time points. The experimental results are shown below. Figure 8 .
[0039] from Figure 8 As can be seen, the wound dressing of Example 1 can promote the healing of cell scratches. After 12 hours of culture, the healing speed of Example 1 is clearly the fastest, and it reaches basic healing by 24 hours. The healing speed of Comparative Example 5 is slower than that of Example 1, indicating that the addition of heparin and vanillin can synergistically promote cell proliferation and migration, thus promoting wound healing.
[0040] (7) Testing of healing ability: Rat wound healing experiment Rats weighing 180-200g were selected for a wound healing experiment. The rats were properly housed and given adequate water and food. After gas anesthesia, the rats' back fur was shaved, and a full-thickness skin wound approximately 1cm in diameter was made using surgical scissors. The control group received sterile saline solution for wound cleaning, while other experimental groups received appropriate wound dressings. Finally, all rat wounds were covered with sterile dressings. The wounds were observed and photographed at predetermined times. The experimental results are as follows: Figure 9 As shown.
[0041] from Figure 9 As can be seen, the wound treated with the wound dressing in Example 1 healed the fastest, and by day 5, scabs had begun to form on the wound. By day 15, the wound size was less than 2 mm in diameter, indicating that it was essentially healed. The wounds treated with the wound dressings in Comparative Examples 2 and 5 healed more slowly, but faster than the blank control group. The wound dressing in Comparative Example 2 did not perform vertical drainage, thus failing to effectively absorb exudate and affecting normal wound healing. In Comparative Example 4, vanillin was not pH-responsively treated, causing it to quickly enter the wound and be lost, instead of waiting for inflammation to subside and then precisely treat the inflamed area. This resulted in the wound environment not maintaining a good physiological state, affecting the healing-promoting ability of heparin. Therefore, the wound dressing prepared using the method of this invention has a better ability to promote wound healing.
[0042] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A biomimetic dressing for skin wounds, characterized in that, It comprises an upper barrier layer, a middle functional layer, and a lower flow-guiding layer that are sequentially cross-linked and stacked; the functional layer is a drug-loaded nanofiber membrane containing a pH-sensitive antibacterial agent and a healing promoter; the flow-guiding layer is a hydrogel layer with a vertically oriented porous structure; and the barrier layer is a photocrosslinked hydrogel layer containing silver-loaded mesoporous silica nanoparticles.
2. The biomimetic dressing for skin wounds according to claim 1, characterized in that, The pH-sensitive antibacterial agent is vanillin linked to polylactic acid-glycolic acid copolymer via hydrazone bonds; the healing promoter is low molecular weight heparin or heparin sodium.
3. The method for preparing the biomimetic dressing for skin wounds according to claim 1, characterized in that, Includes the following steps: S1. Hyaluronic acid and a healing promoter are dissolved in deionized water to obtain an aqueous solution; polylactic acid-glycolic acid and poly(ε-caprolactone) are dissolved in dichloromethane to obtain an organic solution; vanillin-hydrazone-linked polymer is added to the organic solution and stirred to dissolve; the aqueous solution is slowly added to the organic solution, Span 80 is added, and the mixture is stirred and emulsified at 0-4°C to obtain an emulsion; the emulsion is used for electrospinning to obtain a drug-loaded nanofiber membrane; S2. Prepare a 2% sodium alginate oxidase solution and a 2% modified gelatin solution, mix them, and stir for 1-2 hours to obtain a mixed prepolymer solution; subject the mixed prepolymer solution to directional freezing to obtain a vertical porous prepolymer; place the vertical porous prepolymer in a CaCl2 solution to wet it, immediately spread the vertical porous prepolymer on the drug-loaded nanofiber membrane, and then soak it in a 0.3% genipin aqueous solution. Let it stand at 37°C in the dark for 6-12 hours, gently rinse it with deionized water, and air dry it to obtain a double-layer structure dressing; S3. Dissolve methacrylamide gelatin in sterile phosphate buffer to prepare a 5% w / v solution; add photoinitiator LAP, stir until dissolved under light-protected conditions, add silver-loaded mesoporous silica nanoparticles, and perform ice bath sonication to uniformly disperse the silver-loaded mesoporous silica nanoparticles to obtain a prepolymer solution. The prepolymer liquid is poured onto the surface of the double-layer structure dressing. The pouring position is on the other side of the oxidized sodium alginate and modified gelatin polymer film. The prepolymer liquid is spread out with a scraper, covered with a PET film, and then subjected to ultraviolet crosslinking. After cross-linking, the PET film is removed to obtain a dressing sample. The dressing sample is then rinsed with sterile phosphate buffer and sealed in packaging to obtain a biomimetic dressing for skin wounds.
4. The method for preparing the biomimetic dressing for skin wounds according to claim 3, characterized in that, In step S1, the preparation method of the vanillin hydrazone-linked polymer is as follows: polylactic acid-glycolic acid is dissolved in anhydrous DMSO to obtain a polylactic acid-glycolic acid solution; NHS and EDC·HCl are dissolved in anhydrous DMSO and added to the polylactic acid-glycolic acid solution, and the reaction is carried out at room temperature for 6 hours under nitrogen protection to obtain a polymer activation solution; adipate dihydrazide is dissolved in anhydrous DMSO and added to the polymer activation solution, with a mass ratio of adipate dihydrazide to polylactic acid-glycolic acid of 5:1, and the reaction is carried out at room temperature for 24 hours. After precipitation with glacial ether, the product is dried to obtain a white powder; the white powder is dissolved in anhydrous DMSO, vanillin is added, the pH is adjusted to 4-5 with glacial acetic acid, and the reaction is carried out at 40°C for 36 hours under nitrogen protection in the dark to obtain a coupling solution; The coupling solution was dialyzed in the dark and then lyophilized to obtain a vanillin-hydrazone-linked polymer.
5. The method for preparing the biomimetic dressing for skin wounds according to claim 3, characterized in that, In step S1, the mass ratio of hyaluronic acid, healing promoter, polylactic-co-glycolic acid, poly(ε-caprolactone), and vanillin hydrazone-linked polymerization is 1:0.5~1:30~40:3~5:10~15; the amount of Span80 added is 1% of the volume of dichloromethane; the electrospinning parameters are: ambient temperature of 25℃, humidity of 20~40%, voltage of 15~22kV, feed rate of 1.0~2.0mL / h, and receiving distance of 15~20cm.
6. The method for preparing the biomimetic dressing for skin wounds according to claim 3, characterized in that, In step S2, the modified gelatin is prepared as follows: gelatin is dissolved in ultrapure water, heated and stirred in a 50°C water bath until dissolved, and a 2% gelatin solution is prepared; fucoidan is dissolved in acetate-sodium acetate buffer solution to prepare a 2% fucoidan solution, NHS and EDC·HCl are added, and the solution is stirred at room temperature for 30 minutes to obtain a fucoidan activated solution; Fucoidan activation solution and gelatin solution were mixed at a volume ratio of 1:1, and the pH was adjusted to 6.5-7.0 with NaOH. The mixture was reacted at room temperature in the dark for 12-24 hours under nitrogen protection. The mixture was then dialyzed in NaCl solution and then dialyzed in ultrapure water. After freeze-drying, modified gelatin was obtained.
7. The method for preparing the biomimetic dressing for skin wounds according to claim 3, characterized in that, In step S2, the volume ratio of the 2% sodium alginate oxidized solution to the 2% modified gelatin solution is 7:3; the directional freezing step is as follows: the mixed prepolymer liquid is poured into the mold, the mold is placed on the copper platform of the directional freezing device, and unidirectional freezing is performed from bottom to top. The cold source temperature is -78℃, the freezing time is 30~60min, and after the freezing is completed, it is quickly placed at -80℃ for 30min, and then freeze-dried at -50℃ for 24~48h.
8. The method for preparing the biomimetic dressing for skin wounds according to claim 3, characterized in that, In step S3, the preparation method of the silver-loaded mesoporous silica nanoparticles is as follows: Hexadecyltrimethylammonium bromide is dissolved in deionized water, ammonia is added, and the mixture is stirred at 80°C for 30 min. Tetraethyl orthosilicate is slowly added dropwise, with a molar ratio of tetraethyl orthosilicate to hexadecyltrimethylammonium bromide of 4-6:
1. The reaction is continued at 80°C for 2 h. The white precipitate is collected by centrifugation, dispersed in 0.1 mol / L hydrochloric acid solution, and refluxed at 80°C for 24 h. After centrifugation, the precipitate is treated with anhydrous ethyl acetate. Mesoporous silica nanoparticles were obtained by washing with alcohol and deionized water and drying. The mesoporous silica nanoparticles were dispersed in deionized water, and 0.1 mol / L silver nitrate solution was added. The mixture was stirred at room temperature in the dark for 12 h. Then, 0.1 mol / L sodium borohydride solution was slowly added dropwise. The volume ratio of silver nitrate solution to sodium borohydride solution was 1:2~5. The reaction was continued in the dark for 2 h. The precipitate was collected by centrifugation, washed with deionized water, and dried under vacuum at 60 °C to obtain silver-loaded mesoporous silica nanoparticles.
9. The method for preparing the biomimetic dressing for skin wounds according to claim 3, characterized in that, In step S3, the mass ratio of the photoinitiator LAP, silver-loaded mesoporous silica nanoparticles, and methacrylamide gelatin is 1:1:20; the specific parameters for the ultraviolet crosslinking are: wavelength of 365~410nm, and light intensity on the sample surface of 5~10mW / cm². 2 The irradiation time is 30~60s.
Citation Information
Patent Citations
PH response type double-drug-loading bionic wound dressing and preparation method thereof
CN118846188A
Double-bionic dressing with one-way vertical drainage and reverse drug delivery functions and preparation method of double-bionic dressing
CN118976135A